CAPTURING PRE AND POST SECURITY EXCHANGE COMMISSION OF PAKISTAN VOLUNTARY GUIDELINES OF CORPORATE SOCIAL RESPONSIBILITY DISCLOSURE 2013 IMPACT ON FIRM PERFORMANCE IN PAKISTAN - Atta-e-Rabbi, Dr. Faisal Khan, Dr.Muhammad Arif (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
The aim is to study the relationship between corporate social responsibility and its performance in pre and post-regulation of the Security Exchange Commission of Pakistan (SECP) voluntary guidelines 2013 regarding Corporate Social Responsibility (CSR). To conduct this research, secondary data was collected from the annual reports of sample firms for the prescribed period of 2011-2015. For CSR data collection, content analysis was used. Return on Assets (ROA) and Return on Equity (ROE) were used to measure financial performance. The results revealed a significant positive effect of CSR on firm performance. Similarly, results indicated the pre SECP regulation has a significant positive impact on firm performance. The post SECP regulation of CSR also depicts a significant positive effect on firm performance with slight improvement after adopting voluntary guidelines. These study results provide information for understanding the concept of CSR practices in Pakistan’s business environment and will help to improve not only the financial performance of the business community and improve the stakeholder wealth.